Study Shelf Life of Instant Corn Porridge using Arrhenius Method - Wibowo, Fadhrizal Hafidi; Budijanto, Slamet (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2020)
The objective of this research was to observe the quality changes of instant corn porridge during storage and to estimate its shelf life. Parameters that tested to determine the shelf life of instant corn porridge were TBA (Thio Barbituric Acid) number, color change, and the organoleptic characteristic, including aroma and color. The estimation of shelf life was done by storing samples in the incubator with three different acceleration temperatures (35 o C, 45 o C, and 55 o C) for six weeks. Based on the result of this research, the critical parameter to estimate shelf life was the aroma of instant corn porridge powder. The critical value of instant corn porridge powder aroma was 6, which was described as slightly rancid. Arrhenius equation that used to estimate the shelf life of instant corn porridge was ln k = -1808.4(1/T) + 2.932 with the activation energy of 3591.4824  cal/mol. The tested instant corn porridge had 82 days of shelf life at 28 o C of storage temperature.